SISTEM FISIK - NILAI BUDAYA JAWA DALAM ARSITEKTUR WISATA TEBING WATU MABUR DESA MANGUNAN YOGYAKARTA - Alwin Suryono; Nancy Yusnita Nugroho; Budi Widodo P; Chris Hendrawan; Rochana Esti (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract:Â This paper aims to reveal the physical system of Javanese cultural values in the architecture of Tebing Watu Mabur tourist destination. Using the descriptive method, the physical system of the object (figure, layout, materials, activities) and its purpose are observed, then the meaning/value of Javanese Culture is deeply observed with contemplation. The design of the mass-space layout of the tourist site refers to the North-South axis in accordance with the Philosophical axis of Yogyakarta Palace. The design of the grass field considers the harmony of the diversity of user groups and the preservation of the natural environment. The Panggang-pe traditional architectural style was chosen for the stalls and guard posts, following the tradition of village selling places, related to local social and natural relations. The Limasan variety of Pendopo 2 is open to all four sides for social activities of users while enjoying the cliff nature. The combination of traditional-modern materials as a contemporary form of traditional Javanese architecture. The architectural design of this cliff tourism destination means the harmony of nature and the physical system of local Javanese cultural values.Keyword: Traditional, Javanese culture, modern Abstrak:Â Tulisan ini bertujuan mengungkap sistem fisik-nilai Budaya Jawa dalam arsitektur destinasi wisata Tebing Watu Mabur. Digunakan metoda deskriptif, sistem fisik objek (sosok, tata ruang, material, aktivitas) dan tujuannya diobservasi, lalu makna/nilai Budaya Jawanya diamati mendalam disertai perenungan. Desain tata massa-ruang tapak wisata mengacu pada poros Utara-Selatan sesuai dengan sumbu Filosofis Kraton Yogyakarta. Rancangan lapangan rumput memperhatikan keharmonisan dari keberagaman kelompok pengguna dan kelestarian lingkungan alam. Dipilih ragam arsitektur traisional Panggang-pe untuk warung dan pos jaga, mengikuti tradisi tempat berjualan masyarakat desa, terkait relasi sosial dan alam setempat. Ragam Limasan Pendopo 2 terbuka ke empat sisinya untuk aktivitas sosial pengguna sambil menikmati-merasakan alam tebing. Paduan material tradisional-modern sebagai wujud kekinian arsitektur tradisional Jawa. Rancangan arsitektur destinasi wisataÂ tebing ini bermakna keserasian alam dan sistem fisik-nilai Budaya Jawa setempat.Kata Kunci: Tradisional, Budaya Jawa, modern.